Influence of work family balance on job performance, job satisfaction and mental health of electronics craftsmen in Plateau State - Ogbuanya, Chinyere Theresa (International Journal of Research in Counseling and Education, 2022)
This study determined the influence of work-family balance on job performance, job satisfaction and mental health of electronics craftsmen in Plateau State. Six research questions and hypotheses guided the study. A correlational design was adopted for the study. A sample of 171 electronic craftsmen purposively sampled were involved in the study. Four sets of questionnaires were used for data collection. The instrument was face validation by five experts. The reliability coefficient of 0.75 was determined using Cronbach alpha.  Pearson Product Moment Correlation Coefficient was used to analyse the data relating to the research questions while multiple regressions were used for the hypothesis at a criterion level of 0.05 level of significance. The bivariate correlation results show a weak but positive relationship between work-family balance and job performance, and job satisfaction, while it has an inverse influence on their mental health. The result also shows that marital status, age, experience and income level are possible positive moderators of the relationship between work-family and job performance, job satisfaction and mental health. The regression results also show that work-family balance is a positive significant predictor of job performance, job satisfaction and mental health. It also shows no significant interaction effects of marital status, age, experience and income level on the relationship between work-family balance and job performance and job satisfaction. However, the result shows that age and marital status has a significant moderating role on the relationship while experience and income level show significant relationships on the mental health of the craftsmen. It is therefore recommended that work-family balance should be embedded in craftsmen training courses to prepare them well before practice. Craftsmen should also take time to manage their health, as it is only the healthy that can perform well on their job.